Rational Islamists: Islamism and regime preferences in Bangladesh. Issue 4 (18th May 2020) - Fair, C. Christine; Patel, Parina
ABSTRACT: Scholars have long studied whether Islam is compatible with democracy. Quantitative analyses of survey data of Muslim polities have drawn from three broad theoretical and epistemological frameworks: civilizationalist or culturist; modernizationist, and rational choice. In this article, we contribute to this discussion by drawing from survey data from an important but under-studied country: Bangladesh. We use respondent-level data from a novel, nationally representative survey of Bangladeshis which was fielded in 2017 to inveigh upon these debates. Our analysis overwhelmingly undermine civilizationalist and culturalist claims. We find considerable support for modernist assertions that education and urbanization positively correlate with tastes for democracy, but we find little evidence that economic standing does. Our findings lend strong support for rational choice approaches to this puzzle: respondents who want more Sharia also prefer more democracy while those who want more secularism actually want less democracy. We aim to make modest contributions both to the theoretical literature on the relationship between Muslims' religious and political preferences and to the empirical base of knowledge about Bangladesh, an important, yet neglected country.